Efektivitas Social Media Marketing terhadap Produk Makanan Pokok (Staple Food) di Superindo - Dwiasih, Nayda; Yudha, Eka Purna (Universitas Galuh, 2025)
Superindo utilizes Instagram and Tiktok to increase the effectiveness of social media marketing. This study aims to analyze the effectiveness of social media marketing on staple food products at Superindo. This study uses a mix method. Data were collected through questionnaires to 100 Superindo customers who actively use Instagram and/or Tiktok randomly. This study uses the AIDA model to assess the effectiveness of social media marketing. The results showed that the role of Instagram and Tiktok was effective in staple food purchasing decisions. This can be seen from the attention variable value of 3.835, interest 3.85, desire 3.89, action 3.6. The use of social media has become an important factor in shaping consumer purchasing decisions.